The Impact of Prenatal Diagnosis and Treatment on Early Neonatal Problems - Selcan Sinaci; Gulsum Kadioglu Simsek; Bedri Sakcak; Izzet Ozgurluk; Fuat Emre Canpolat; Dilek Sahin (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Obstetric problems have detrimental effects on both pregnancy and newborn. We aimed to examine the relationship between pregnancy complications and newborn morbidities.